Vocabulary Analogy as Instructional in Enhancing Reading Comprehension - Fajrianor Fajrianor (Universitas PGRI Semarang, 2018)
This research was designed to find out the effects of vocabulary analogy to reading comprehension of seventh grade students of State Junior High School 9, Yogyakarta, Indonesia. Specifically it sought to answer the following questions: 1) How is the effects in reading comprehension of the students taught with Vocabulary Analogy or without vocabulary analogy? 2) Is there a significant difference in the reading comprehension between the control and experimental groups based on the pre-test and post-test results? A test was conducted for control and experimental groups before and after the treatment process. T-test was computed to reveal whether there was a significant difference in the pre-test and post-test results of the control and experimental groups. Findings of the research were: 1) The use of vocabulary analogy improved students’ reading comprehension 2) The computed T value based from the results of pre-test in the control and experimental groups is 0.130, lower than T tabular value of 1.996. This result accepts the null hypothesis that there is no significant difference in the results of pre-test of control and experimental groups. Moreover, treatments were given to control and experimental groups after the pre-test, control group was taught without vocabulary analogy and experimental group was taught with vocabulary analogy before the post-test for each group. The computed T value in the post-test of the control and experimental groups is 11.15, higher than T tabular value of 1.996 at5% level significance. This result rejects the null hypothesis that there is no significant difference in the results of pre-test and post-test of control and experimental groups. Based on findings, the following conclusions were drawn: 1) The use of vocabulary analogy had significantly influenced students’ reading comprehension particularly of the experimental group 2) There is significant difference in the post-test results of the control and experimental groups. Null hypothesis was rejected since the computed T value was higher than the T tabular value.